(untitled) (International Journal of Built Environment and Sustainability, 2025)
Currently, almost half of the world’s population lives in urban areas, and it is projected that by 2050, about one-third of the global population will reside in cities. This significant urbanization trend is particularly noticeable in towns in the Global South. One such town is Sialkot, known as the city of Iqbal, an important city in the Punjab province of Pakistan. Sialkot has experienced significant physical expansion to accommodate its growing population. As land is a crucial resource for the city’s expansion and residential development, Saddar Bazaar, located in the Sialkot Cantonment area, has become the central hub of this historic city. However, this rapid and uncontrolled urbanization has presented various challenges, including haphazard urban development, unregulated construction, and inappropriate changes in building function. This study examines the compatibility of traditional building functions, layouts, and components within Saddar Bazaar, Sialkot Cantt. It also investigates how changes in a building’s function affect its components and, on a broader scale, how it impacts the residents. This study follows a qualitative research approach and employs a field survey as the primary data collection method. The survey combines a questionnaire and direct observation to achieve the research objective, highlighting the problems and challenges associated with urban development and tracking the transformation of a residential area into a commercial one. Data was collected by distributing questionnaires to a hundred residents who had lived in different parts of Sialkot for over two decades. Site observations were conducted at various times of the day from late 2021 to spring 2022. Statistical data analysis was performed using Microsoft Excel, and thematic analysis was used to group the qualitative findings. Based on the research findings, it can be concluded that features like Baraza exemplify the typical characteristics and layout of the transformation. Furthermore, this study proposes alternative solutions to address the challenges related to urbanization and commercialization, benefiting policymakers, academics, and citizens alike.